The Moral Value of Ibu Prani's Character in Building Character Education in the Film Budi Pekerti by Wregas Bhanuteja - Jesika Elviana Sambokarua; Gazali Gazali; Ade Nurul Izatti G. Yotolembah; Pratama Bayu Santosa; Nirmayanti Nirmayanti (Civiliza Publishing, Indonesia., 2026)
This research aims to describe the form of moral values possessed by the character of Mrs. Prani in the film Budi Pekerti. This study uses a qualitative descriptive method with data sources in the form of dialogue in the film Budi Pekerti by Wregas Bhanuteja. Data collection techniques are carried out through observation, recording, and documentation. Data analysis uses Nurgiyantoro's theory of moral values which divides moral embodiment into three aspects, namely the relationship between humans and themselves, the relationship between humans and other humans, and the relationship between humans and God. The results of the study show that the character of Mrs. Prani has three forms of moral values. First, the moral value of human relationships with oneself which includes standing firm, honest, firm, courageous, and patient. Second, the moral value of human relationships with other human beings which includes caring for others, appreciation, gratitude, and love. Third, the moral value of human relationship with God which is manifested through gratitude. These moral values are reflected in the attitudes, actions, and dialogues of Ibu Prani's characters who are able to defend the truth, respect others, and show social and spiritual concern. The findings of this study show that the figure of Mrs. Prani can be used as an example in building character education, especially in instilling the values of honesty, responsibility, and care for students.